A review of global cassava (Manihot esculenta Crantz) production trends, post-harvest physiological deterioration (PPD) challenge, and control strategies - Dankwa, Kwame Obeng; Gimode, Winnie Riziki Adu; Olasanmi, Bunmi (Springer Nature, 2025)
Cassava is a versatile crop with wide-ranging applications across both food and non-food industries. Over the past five years cassava has seen a steady rise in global production. Africa stands out as the leading producer with three of the top five cassava-producing countries (Nigeria, DR Congo, Ghana) located on the continent, highlighting the crop’s vital role in African agriculture. However, this leading position is primarily due to the expansion of cultivation areas, a strategy that is not sustainable. A significant challenge in global cassava production is post-harvest physiological deterioration (PPD), which causes rapid deterioration of cassava roots after harvest. Unlike other root and tuber crops such as yam, cocoyam, sweet potato, and potato, PPD is uniquely rapid in cassava and significantly impacts its marketability and processing quality. Addressing the issue of PPD is crucial to the crop’s commercial viability. Developing PPD-tolerant cassava varieties could significantly transform the cassava value chain. This review examines global cassava production trends over the past five years and identifies challenges to its growth. It discusses strategies such as developing PPD tolerant cassava varieties aimed at strengthening the cassava value chain and enhancing global food security. Additionally, it examines the economic impact of PPD, current efforts to mitigate it, and the need for a uniform PPD phenotyping approach for better assessment and diagnosis. Addressing these challenges could unlock the potential of cassava as a key driver of sustainable development and improved food security.